Differences in soil ammonia oxidizing bacterial communities under unpalatable (Stellera chamaejasme L.) and palatable (Elymus nutans Griseb.) plants growing on the Qinghai Tibetan Plateau. (May 2020) - Ma, Jianguo; Bowatte, Saman; Wang, Yufang; Newton, Paul; Hou, Fujiang
Abstract: A comparison of ammonia oxidizing bacterial (AOB) communities in the root zone soil of the unpalatable weedy species Stellera chamaejasme L . and the palatable species Elymus nutans Griseb. showed Stellera had different AOB present and that these AOB were characterized by having low ammonia oxidation rates. This difference is consistent with a lower nitrification rate in Stellera soils when urine was added to simulate the dynamics in animal urine patches. Lower nitrification is expected to reduce losses of nitrogen (N) to the environment leading to greater N availability for plant growth. This may provide a competitive advantage for Stellera and help explain its success as an invasive plant in the Qinghai Tibetan Plateau. Interestingly, it also implies a reduced environmental footprint of this apparently undesirable species through reduced emissions of nitrous oxide and leaching of nitrate. Highlights: Soil AOB communities are different under Stellera than under Elymus. Nitrification is slower in soils under Stellera than in soils under Elymus. The lower nitrification in soils under Stellera resulted in a conserved N cycle. Conserved N cycle in Stellera soils may confer greater competitiveness to the plants.